Pengaruh Volume Terhadap Harga Saham pada Trading Activities PT. BCA Tahun 2017 dengan Menggunakan Metode Theil - Arshie Nur Aisyah; Helma Helma (UNIVERSITAS NEGERI PADANG, 2018)
Abstract− The relationship between the volume and stock price is used as a reference by investors in buying and selling stock. But many of the novice investors don’t know the relationship between stock prices and volumes, resulting in errors in conducting stock transactions. Research was conducted to see the effect of volume on stock prices by using the theil method to match the regression line. This study produced a regression model. The slope coefficient of the regression model, 95% will be between 11.92799 to 24.91132 and the determination coefficient is 0.99530761 which indicates that 99.53% of the volume can explain stock prices while the rest is influenced by other variables not included in the model.